Pengaruh Modernisasi Terhadap Bahan Bangunan Hunian Tradisional Di Desa Adat Tenganan, Kabupaten Karangasem, Bali - Indra, I Gede Bagus Rae (Universitas Dwijendra, 2020)
Tenganan Traditional Village is a Bali Aga Village located in Karangasem Regency. As a cultural village tourism object, Tenganan Traditional Village is unique in the form of a spatial arrangement pattern with unique traditional building architecture, traditions and cultural activities of the community, as well as villagers' handicrafts such as woven or bamboo, carvings, and paintings on palm leaves as well as gringsing woven fabric. In line with the times and the rapid development lately there have been concerns about the continuation of development in the Tenganan Traditional Village, resulting in many changes to the residential buildings, especially in building materials. The condition of the Traditional Village which has started to leave materials for traditional buildings and switch to modern building materials. These changes caused the loss of the traditional values of the Tenganan people which became the core of the local community architecture. So it needs special attention and efforts in preserving the architectural values of traditional Tenganan houses. So that the existence of traditional houses and the uniqueness of the village can be maintained and still show the traditional values of the traditional houses of Tenganan Village, with new buildings that will be occupied by the community. Some things that have experienced the influence of modernization are in terms of roof, wall and bataran building materials. This requires joint efforts by the government and local communities to preserve the development of traditional houses related to traditional traditions in the Tenganan Traditional Village so that the construction of traditional houses is sustainable.